Lathrolestes buccinator Holmgren 1857 - Reshchikov, Alexey (Zenodo, 2012)
Lathrolestes buccinator (Holmgren, 1857) Figs 26–29 Perilissus vollenhoveni (Gribodo, 1880). NHRS Diagnosis. This species differs from the closely related L. tripunctor by the elongate first metasomal tergum (Fig. 28), without longitudinal carinae and longitudinal lateral impressions, and the black face in the female; from the closely related L . erythrocephalus this species differs by its yellow tegulae. Material. 2 females Finland; 2 females France; 1 male Slovenia; 5 females, 3 males Ukraine; 1 male Armenia; 1 male Azerbaijan; Russia: 5 females Leningrad reg.; 1 male Smolensk reg.; 2 males Krasnodar Territory; 2 females, 5 males Krasnoyarsk Territory; 1 female Buryatia; 1 female Kamchatka; 2 males Khabarovsk Territory; 1 male Sakhalin; 2 males Primorsky Territory (ZIN RAS). Distribution. Palearctic. Published as part of Reshchikov, Alexey, 2012, Lathrolestes (Hymenoptera, Ichneumonidae) from Central Asia, with a key to the species of the tripunctor species-group, pp. 24-44 in Zootaxa 3175 on page 28, DOI: 10.5281/zenodo.246266